Efeito da assimetria flutuante em uma comunidade de Odonada - Valle, Egon Luis Vilela do (2019)
Fluctuating asymmetry (FA) is an indicator of the differences between the sides of an organism, often attributed to developmental stress. This study aimed to analyze FA at a community level for two suborders of Odonata: Anizoptera and Zygoptera. The focus was on exploring the relationship between FA and fitness-related traits like muscle mass and body fat. Specimens were collected from a local savanna reserve, and their morphometric values were measured to calculate FA. Linear regressions and GLM analysis were used to quantify the relationships between the variables. The results revealed a negative correlation between FA, muscle mass, and wing area, but only for Zygoptera. No association was found between fat reserves and FA. The significant results in Zygoptera suggest that this symmetric instability may be linked to specific physiological and anatomical factors. The FA observed in Zygoptera occurred during the formation phase of flight muscles, indicating stress during the aquatic phase. Unlike muscle mass, fat reserves experience atrophy post-emergence, leaving minimal reserves to the adult phase. It is likely that FA does not cause significant harm to the overall well-being of individuals. However, in Zygoptera, FA may impact fitness performance due to its relationship with wing area and muscle mass, which are vital for reproductive activities like combat and foraging. Thus, FA could affect the fitness performance of Zygoptera but not the general welfare of individuals.